Enhancing Product Support Performance and Revenue Through Localized Service Point: Case Study at PT XYZ in Tenggarong - Rizky Awalul Ramdani; Gembong Baskoro; Dwityapoetra S. Besar (ILTEK : Jurnal Teknologi, 2026)
This study aims to analyze the impact of establishing a localized service point on after-sales performance in the mining sector. A case study was conducted at PT XYZ in Tenggarong, which faced issues with low On-Time In-Full (OTIF) delivery (~83%), far below the corporate target of 90%. As a result, PT XYZ captured only about 50% of PT PKSM’s spare parts sales potential. Using a mixed-method approach (DMAIC, customer satisfaction survey, IRR/NPV analysis), the findings show that developing a local service point can improve OTIF to ~95%, reduce downtime by more than 70%, increase customer satisfaction scores (from 2.8 to 4.3 on a 5-point Likert scale), and raise annual revenue by up to 74% (IDR 24 billion). Financial analysis confirms feasibility, with an IRR of ~75% and positive NPV even under pessimistic scenarios. Thus, a localized support point is proven to be both feasible and strategic for enhancing service performance and strengthening market position.